Effects of Irrigation with Treated Wastewater on Root and Fruit Mineral Elements of Chemlali Olive Cultivar. (11th June 2014) - Bedbabis, Saida; Ben Rouina, Béchir; Boukhris, Makki; Ferrara, Giuseppe
Abstract : Twenty-year-old "Chemlali" olive trees trained to vase and rainfed were investigated in either "on" (2004) or "off" (2003) year. A randomized block design with three blocks and three treatments was used and each experimental plot consisted of nine olive trees. Three treatments were applied: (1) rainfed conditions (RF, used as control treatment); (2) irrigation with well water (WW); and (3) irrigation with treated wastewater (TWW). Irrigation with TWW led to a significant increase of root N, P, Ca, Zn, Mn, Na, and Cl concentrations, in particular in the on-year. Data showed significant differences, between the two years, for the concentration of the mineral elements in the roots, with general lower values in the on-year, probably as a consequence of nutrients movement upward in the tree. Fruit N, P, K, Zn, Mn, and Cl contents were significantly higher in TWW irrigated trees with respect to both RF and WW trees, whereas similar values for Ca, Mg, Na, and Cl contents were measured for WW and TWW irrigated trees. The irrigation with TWW allowed to reuse problematic waters and to save nutrients inputs in the olive orchard thus moving towards a more sustainable management of olive orchards in countries where water is the major limiting factor for agriculture.